Senam Menuju Lansia Sehat dan Bugar - Margareta Haiti; Novita Anggraini; Aprida Manurung (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Old age is a natural process experienced by both men and women who have reached the age of 60 years and over. Aging means that you have experienced a process of decline both physically and mentally. The elderly can still be productive when they have a healthy and fit body. Health can be maintained through a balanced nutritional intake and through physical activities such as gymnastics. Efforts to prevent disease in the elderly can be carried out through health checks. As for the purpose of this activity, the elderly are expected to be able to live healthy and fit to carry out their daily life. Methods: carry out elderly exercise together followed by health education and blood pressure checks for elderly mothers and fathers at the Sumarah Sukomoro Nursing Home, totaling 31 people. The results of blood pressure measurement showed that 33.3% had pre-hypertension (BP 120-139mmHg), 20% had grade 1 hypertension (140-159 mmHg), and 13.3% had grade 2 hypertension (â‰¥160 mmHg).